Value Of Religiusity In The Mujahadah Tradition; Study at Ulul Albab Nganjuk Islamic Vocational School - Hilma Dian Wulandari; A. Jauhar Fuad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This paper aims to examine the values ​​of religiosity through the mujahadah tradition at Islamic Vocational School Ulul Albab Nganjuk. This research departs from two research questions,